Implementing Digital Technology in Public Financial Information Presentation - Dwiyanti, Erina; Prayudi, Made Aristia (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
The implementation of digital technology has become an essential initiative in improving transparency, efficiency, and accountability in the management and dissemination of public financial information. This study aims to examine the benefits, challenges, and strategic considerations associated with the adoption of digital technology in presenting public sector financial data. Using a qualitative approach based on a comprehensive literature review, the study highlights how digitalization enables real-time access to financial information, minimizes the risk of human error, and enhances public trust in financial governance processes. Despite these advantages, the research also identifies persistent challenges, such as inadequate infrastructure, limited technical capacity, and uneven digital readiness across government institutions. To address these issues, the study proposes several practical recommendations, including the development of supportive regulatory frameworks, increased investment in digital infrastructure, and the implementation of targeted training programs for public sector personnel. Overall, this research contributes both theoretical understanding and practical insights to advance the digital transformation of public financial management.